LEGAL ORGANIZATION OF INFORMATION SECURITY: A SYSTEMATIC APPROACH - Kunev, Yurii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to study the theoretical foundations and legislation of Ukraine in the field of information security and the directions of their development. Research methods: a systemic approach to creating a theoretical picture of the object and applying a methodological scheme of knowledge about the object and about the knowledge that describes it; comparative legal and doctrinal knowledge of legislation, as well as a method of generalizing and modeling new theoretical knowledge of information law. Results: problems of further development of information security are identified and theoretical approaches for their solution are proposed. For a systematic solution to the set of identified problems, it is necessary to determine the components of the information system, its subsystems. Examples of subsystems of administrative activity and its information components are given. Correct definition of the boundaries of the system will contribute to the correct definition of the directions of ensuring information security and its legal support. The legal organization of information security means an interdependent process of interaction between the information and legal subsystems of activities. The subject of the legal organization of information security will be the legal organization of information activities and information components of the administrative activities of public authorities in the norms of legislation. Discussion: the criteria that most influence the legal organization of information security and the models of the norms of information law necessary for acquiring the qualities of information legislation of Ukraine are determined.